Clear Lens Extraction in Glaucoma (Is it still a controversy?): Doi: 10.36351/pjo.v36i2.1025 - Ahmad, Syed Shoeb (Pakistan Journal of Ophthalmology, 2020)
The lens appears to play a strategic role in the etiopathogenesis of glaucoma. This is not a new concept. In 1891 Priestley Smith had noted that some patients diagnosed with glaucoma demonstrated shallow anterior chambers even before the development of the disease (glaucoma). He concluded that this feature could be attributed to the disproportion between the size of the eyeball and the lens1. Lowe (1969) mentioned that the anatomical basis of primary angle closure glaucoma (PACG) lies in two important “constitutional” factors (lens position and thickness) and two other factors of lesser importance related to advanced age (increase in lens thickness and anterior lens displacement)2.